A critical analysis of issues relating to raising achievement in number at Key Stage 1 - Munns, Sebastian (2016)
This dissertation seeks to consider how to raise achievement in number at Key Stage 1, investigating the issues relating to number and subsequently considering how an intervention with a research-informed personalised teaching approach might affect pupil performance at Key Stage 1. The dissertation also explores mathematics teachers’ perspectives on the impact of current school-based interventions in facilitating increased achievement in number at Key Stage 1. The sample for the intervention based on a research-informed personalised teaching approach comprised of ten children from Key Stage 1, divided into two groups of five children for maximum impact. Nine out of ten children improved their score by an average increase of 22% over the course of the ten-week intervention. A sample of ten mathematics teachers, at the same school as the pupils study, were asked their views on the impact of current school-based interventions in facilitating increased achievement in number at Key Stage 1. The Head of Maths, both members of the Senior Leadership Team, both class teachers and all four teaching assistants expressed the view that ‘personalised learning’, ‘targeted intervention’ and ‘1:1 intervention’ all have a positive impact on raising achievement in number at Key Stage 1.